A Case of Sporadic Creutzfeldt-Jakob Disease Presenting as Conversion Disorder. (3rd May 2017) - Yegya-Raman, Nikhil; Aziz, Rehan; Schneider, Daniel; Tobia, Anthony; Leitch, Megan; Nwobi, Onyi
Abstract : Background . Creutzfeldt-Jakob disease is a rare disorder of the central nervous system. Its initial diagnosis may be obscured by its variable presentation. This case report illustrates the complexity of diagnosing this disease early in the clinical course, especially when the initial symptoms may be psychiatric. It offers a brief review of the literature and reinforces a role for consultation psychiatry services. Methods . PUBMED/MEDLINE was searched using the terms "Creutzfeldt-Jakob disease", "psychiatric symptoms", "conversion disorder", "somatic symptom disorder", "functional movement disorder", and "functional neurologic disorder". Case . The patient was a 64-year-old woman with no prior psychiatric history who was initially diagnosed with conversion disorder and unspecified anxiety disorder but soon thereafter was discovered to have Creutzfeldt-Jakob disease. Discussion . This case highlights the central role of psychiatric symptoms in early presentations of Creutzfeldt-Jakob disease. Still, few other cases in the literature report functional neurological symptoms as an initial sign. The consultation psychiatrist must remain alert to changing clinical symptoms, especially with uncharacteristic disease presentations.